IMMU-71. EVALUATING THE COMPATIBILITY OF TUMOR TREATING ELECTRIC FIELDS WITH KEY ANTI-TUMORAL T CELL FUNCTIONS. (5th November 2018) - Diamant, Gl; Simchony, Hadar; Shiloach, Tamar; Globerson-Levin, Anat; Eshhar, Zelig; Grossman, Rachel; Ram, Zvi; Volovitz, Ilan
Abstract: BACKGROUND: Combining Tumor Treating electrical Fields (TTFields) with immunotherapy is a rational approach due to their different mechanisms of action (MOA) and to TTFields' ability to induce immunogenic cell death (ICD). Conversely, TTFields may interfere with immune functions critical for effective T cell responses. METHODS: T cells from healthy donors' peripheral blood or from viably dissociated glioblastoma samples were cultured under normal or TTFields conditions, with or without superantigen-stimulation. Eight-color flow cytometry was used to assess T cell responses by monitoring select pivotal antitumoral functions: proliferation (CFSE), IFNγ secretion, cytotoxic degranulation (CD107a), activation/exhaustion (PD1) and viability. Direct cytotoxicity was evaluated using chimeric antigen receptor (CAR) T cells. RESULTS: The viability of stimulated T cells that attempted to proliferate decreased under TTFields, in line with TTFields' MOA. Small or no reductions in viability were found in activated T cells that did not attempt to proliferate and in unstimulated T cells. The functionality of stimulated peripheral-blood T cells and tumor-infiltrating T cells (TILs) under TTFields was unhindered: T cells exhibited comparable PD1 upregulation, IFNγ secretion and CD107a expression as controls. T cell polyfunctionality, associated with effective antitumoral responses, was retained under TTFields conditions. PD1-expressing TILs, a subset containing most of the tumor antigen-specific TILs, exhibited unaltered viability and functionality under TTFields. CAR T-cells, which utilize the same killing machinery as unmodified T cells, exhibited unaltered cytotoxic capability under TTFields. Gene expression analysis of GBM tissues obtained before and after patients' treatment with chemoradiation or chemoradiation+TTFields, demonstrated, in TTFields treated patients, increases of transcripts associated with antitumoral responses (CD8, NKp46, GranzymeB, Perforin), and decreases in protumoral-associated myeloid-compartment transcripts (CD66b, CD163, HLADR) CONCLUSIONS: All antitumoral T cell functions examined, with the exception of proliferation, were unhindered by TTFields. Our findings warrant the further preclinical and clinical investigation into the combination of TTFields and immunotherapy.